The narrowing of the US gender earnings gap, 1959 - 1999: a cohort-based analysis - Catherine Weinberger; Peter Kuhn (Institute for the Study of Labor (IZA), 2006)
Using Census and Current Population Survey data spanning 1959 through 1999, we assess the relative contributions of two factors to the decline in the gender wage gap: changes across cohorts in the relative slopes of men's and women's age-earnings profiles, versus changes in relative earnings levels at labor market entry. We find that changes in relative slopes account for about one-third of the narrowing of the gender wage gap over the past 40 years. Under quite general conditions, we argue that this provides an upper bound estimate of the contribution of changes in work experience and other post-school investments (PSIs) to the decline of the gender wage gap.
Keywords: J7; 330; women; United States; experience; wages; Frauenarbeitslohn; Lohndrift; USA; Frauenarbeitslohn; Lohndrift; USA; Gleichberechtigung; Geschlechterdiskriminierung